Beyond impact assessment: an iterative model of social assessment for the climate transition - Holly Jean Buck; Sara Nawaz (Environmental Research: Energy, 2025)
Climate action demands massive changes in energy systems and land use, and there is growing demand for attention to the social impacts of the new infrastructures and enabling policies for climate transition technologies. Companies and policymakers are leaning on the concept of social impact assessment (SIA) to address social considerations. However, SIA practices were never fully institutionalized, and current practice is not fit-for-purpose for the climate transition. A new methodology for social assessment that goes beyond SIA is needed to enable effective—and responsible—planning and public deliberation about trade-offs in climate technologies and policies. This new methodology would not only examine the impacts of new technologies, but it would do so at scale and throughout supply chains, and evaluate how the technology might be applied in various social and policy scenarios. Here, we outline a new model for iterative social assessment that goes beyond SIA and earlier efforts in integrated assessment to incorporate necessary features of other assessment approaches such as technological assessment, environmental justice assessment, and social life cycle assessment. The paper details how research and practice communities can create the scientific foundation for this model and describes the next steps key institutions should take towards building this necessary social infrastructure for the climate transition.